Neurorestorative Effects of a Novel Fas-Associated Factor 1 Inhibitor in the MPTP Model: An [18F]FE-PE2I Positron Emission Tomography Analysis Study - Park, Hyun Soo; Song, Yoo Sung; Moon, Byung Seok; Yoo, Sung-Eun; Lee, Jae Moon; Chung, Yeon-Tae; Kim, Eunhee; Lee, Byung Chul; Kim, Sang Eun (Frontiers in Pharmacology, 2020)
Fas-associated factor 1 (FAF1), a Fas-binding protein, is implicated in neuronal cell death in Parkinson’s disease (PD). We examined the effects of a novel FAF1 inhibitor, KM-819, in dopaminergic neurons in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model using [18F]FE-PE2I positron emission tomography (PET). The MPTP model was generated with subacute MPTP treatment (20 mg/kg/day, i.p.) for 5 consecutive days in C57bl/6J mice. This study included three groups: the control group (treatment with saline only), the MPTP model group with KM-819 treatment (20 mg/kg/day p.o.) for 6 days, and the MPTP model group without KM-819 treatment. [18F]FE-PE2I PET studies were conducted in the same animals before and after MPTP with or without KM-819 treatment to monitor changes in striatal dopamine transporter activity indicated by non-displaceable binding potential (BPND) of [18F]FE-PE2I, and the expression levels of tyrosine hydroxylase were assessed using immunohistochemistry before and after KM-819 treatment. After MPTP injection, decreased striatal BPND was observed in the MPTP model group compared with the control group. Striatal BPND increased in the MPTP model group with KM-819 treatment, but not in the MPTP model group without KM-819 treatment. The tyrosine hydroxylase expression levels also significantly increased in the MPTP model group with KM-819 treatment compared with the control group. This study indicates that inhibition of the Fas-mediated cell death pathway by KM-819 has neurorestorative effects in striatal dopamine neurons in the MPTP model. Further studies would be needed to investigate the potential of KM-819 as a therapeutic drug for PD treatment.